POLA SEBARAN KERUANGAN DAN STRATEGI PENANGANAN INDUSTRI KECIL TAHU DI KABUPATEN NGANJUK - Sukma, Fitri Hana; Indrayati, Ariyani (Universitas Negeri Semarang, 2025)
This study aims to analyze the spatial distribution patterns of small-scale tofu industries, identify the challenges they face, and formulate appropriate strategies for handling it. The research employs a quantitative descriptive approach, utilizing Moran’s I spatial analysis to determine the distribution pattern of tofu industries and SWOT analysis to handle strategic recommendations.The findings indicate that small-scale tofu industries in Nganjuk Regency exhibit a clustered distribution pattern. The main challenges faced by industry players include limited capital, dependence on imported raw materials, a shortage of skilled labor, the use of traditional production technologies, and suboptimal marketing strategies. Based on the SWOT analysis, the recommended strategies for handling the small-scale tofu industry in Nganjuk Regency include improving access to capital through government assistance programs, diversifying product based the innovation, and leveraging digital marketing to expand market reach. The implementation of these strategies is expected to foster more sustainable growth and enhance the industri’s contribution to the regional economy.